THE ROLE OF INFORMATION TECHNOLOGY IN IMPROVING THE EFFICIENCY OF ACADEMIC PORTALS: A CASE STUDY IN SOUTH TANGERANG CITY - Sitti Aliyah Azzahra (Journal Of Applied Multidisiplinary Studies, 2024)
The rapid advancement of Information Technology (IT) has presented challenges and opportunities for higher education institutions in managing academic administrative processes. Academic portals have become essential in supporting various activities, such as enrollment, grade submission, and student communication. However, without proper optimization, these portals often face issues like slow response times, user difficulties, and inadequate features. This study aims to explore how IT can be optimized to enhance the operational efficiency of academic portals, focusing on higher education institutions in South Tangerang. Using a qualitative approach, this research involves interviews with portal administrators, students, and lecturers, as well as case studies at several universities in the region. The findings indicate that integrating advanced IT solutions significantly improves the speed, usability, and overall efficiency of academic portals. Key factors include enhanced server performance, automated processes, and improved user interface design. Optimizing IT in academic portals can lead to substantial gains in operational efficiency, reduce administrative workload, and improve user satisfaction. Recommendations include further technological development and user training to maximize system potential.